1985
DOI: 10.1104/pp.79.3.734
|View full text |Cite
|
Sign up to set email alerts
|

H+ Extrusion and Potassium Uptake Associated with Potential Hyperpolarization in Maize and Wheat Root Segments Treated with Permeant Weak Acids

Abstract: ABSTRACFThe rapid uptake of weak acids permnt in the unchaged form is accompanied in maize and wheat root segments by a hyperpolariztion of the transmembrane electrial potential and an increase in K uptake, suggesting a stimulation of the plasmalemma H' pump. The evalation of weak acid-induced H' extrsion must take into account the alkalinization of the medium due to the rapid uptake of the uncagd form of the acid, partially masking the proton pump-mediated extrusion of H+. The data corrected for this interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
21
0

Year Published

1986
1986
1989
1989

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…A transient overshoot was observed for both Em and pH upon acetate withdrawal, but an explanation is uncertain. These parallel responses to acetate by Em and pH (though observed in different tissues) support the common opinion that weak acids enhance an electrogenic proton extrusion (7,9,13,16). …”
supporting
confidence: 60%
See 2 more Smart Citations
“…A transient overshoot was observed for both Em and pH upon acetate withdrawal, but an explanation is uncertain. These parallel responses to acetate by Em and pH (though observed in different tissues) support the common opinion that weak acids enhance an electrogenic proton extrusion (7,9,13,16). …”
supporting
confidence: 60%
“…Hyperpolarizations induced by weak acids are commonly interpreted to reflect enhanced proton extrusion caused by acidification of the cell interior (7,9,13,16). Additional support for this interpretation is provided by previously unreported data from oat coleoptiles.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Since it has been shown that electrogenic H+ extrusion in vivo (6,15,28) well as the plasma membrane H+-ATPase in vitro (10,14,20,29) are strongly stimulated by small decreases in pH in the range of cytoplasmic pH values, these data have been interpreted as indicating that FC-induced stimulation ofelectrogenic H' extrusion is a consequence of the acidification of the cytoplasm (5,7,15).…”
mentioning
confidence: 99%
“…Moreover, Romani et al (28) have shown that the effects of FC on H' extrusion, K+ uptake, and hyperpolarization of A* are clearly synergistic with those of weak acids which decrease the cytoplasmic pH, thus strongly suggesting that the two agents influence the H+-pump through different mechanisms. While the FC-induced change of the cytoplasmic pH remains open to investigation, it seems very unlikely that it represents the primary event leading to the stimulation of H+ extrusion.…”
mentioning
confidence: 99%